2004
DOI: 10.1007/s10592-004-1985-3
|View full text |Cite
|
Sign up to set email alerts
|

Inferring demographic processes from the genetic structure of a metapopulation of Boltonia decurrens(Asteraceae)

Abstract: Boltonia decurrens (Asteraceae), a federally listed, threatened floodplain species, requires regular flooding for suitable habitat and seed dispersal. Flood suppression and habitat destruction have resulted in fewer than 25 populations remaining throughout its 400 km range. Because individual populations are widely interspaced (>10 km) and subject to frequent extinction and colonization, seed dispersal along the river, not pollen flow, is likely the primary determinant of population genetic structure. We used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 40 publications
1
40
0
Order By: Relevance
“…In Boltonia decurrens, a threatened floodplain species that requires regular flooding for suitable habitat and seed dispersal, an F ST ¼ 0.098 was observed (DeWoody et al, 2004). In Populus nigra, a riparian pioneer tree species that was studied along the Drô me River, the F ST value was 0.047 (Imbert and Lefèvre, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Boltonia decurrens, a threatened floodplain species that requires regular flooding for suitable habitat and seed dispersal, an F ST ¼ 0.098 was observed (DeWoody et al, 2004). In Populus nigra, a riparian pioneer tree species that was studied along the Drô me River, the F ST value was 0.047 (Imbert and Lefèvre, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mixing of seeds from different source populations through water transport may not be uncommon in natural river systems (Kudoh and Whigham, 2001). DeWoody et al (2004), for example, showed that colonization events in a metapopulation of B. decurrens involved seeds from at least three to five source populations. Similarly, colonization of islands by the weedy Silene dioica through water transport also involved a mixture from several locations (Giles and Goudet, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the persistence of simulated populations of the riparian gravel shore plant Aster kantoensis is dependent on Xood frequency and the time until perennial invasion (Shimada and Ishihama 2000). Another riparian plant, Boltonia decurrens, also requires regular Xooding for suitable habitat creation and seed dispersal along the river (DeWoody et al 2004). In plants, local populations increase in habitats to which they are well adapted and decline in habitats to which they are poorly adapted.…”
Section: Dynamic Landscapes and Habitat Trackingmentioning
confidence: 99%
“…Patchy population structure seems to be typical of many riparian plant species (Menges 1990;Shimada and Ishihama 2000;DeWoody et al 2004;Jäkäläniemi et al 2005). Spatial and temporal variation in stream Xow creates heterogeneous habitat structures, and small-scale disturbances remove vital parts of plants (e.g., inXorescences) or entire plants.…”
Section: Introductionmentioning
confidence: 99%